Introduction: The Plurality of Prosperity Theologies and Pentecostalisms - Attanasi, Katherine (Pentecostalism and Prosperity: The Socio-Economics of the Global Charismatic Movement, 2012)
This book explores the socioeconomic implications of the prosperity gospel in the lives of Pentecostal/charismatic Christians. The volume offers a robust picture of prosperity teachings, which are sometimes called the “health and wealth” gospel. The authors provide thick descriptions of prosperity theologies and their functions within local communities around the globe—for example, in Latin America, Eastern Europe, Southeast Asia, and sub-Saharan Africa. Pentecostalism and Prosperity is geared toward a wide readership. The contributors employ a variety of methodological approaches including theology, ethics, history, and the social sciences. The in-depth case studies will benefit specialists in global Christianity as well as sociologists, anthropologists, economists, and others interested in the intersection of religion and economic life. With a diverse audience in mind, I begin with a brief overview defining terms and providing background on Pentecostal Christianity and prosperity messages. I then introduce each chapter and highlight three overarching themes.
paid
Keywords: Biblical Text; Charismatic Movement; Prosperity Gospel; Protestant Ethic; Renewal Movement